O trabalho do juiz gestor do Tribunal de Justiça do Estado do Maranhão e as implicações para sua saúde e subjetividade - RODRIGUES, Railson de Oliveira (2018)
The present dissertation brings the results of the research on the psychodynamic pleasure and suffering in the work of management attributed to the judges of the Counties of the Court of Justice of the State of Maranhão (TJMA). Through the epistemological bias of the psychodynamics of work founded by Christophe Dejours and also based on historicaldialectical materialism, we will discuss how the work of the TJMA Judges undergoes management tools and how they can deal with the peculiarities and challenges of team management, materials and work processes. The specific objectives are: characterize the management model of the TJMA, understand the specificities of the organization and working conditions in their districts, identify the factors that generate pleasure and suffering in the work of the judges-managers and the mediation strategies implemented by these workers to face the adversities and difficulties of daily work. The methodology used was the semi-structured interview with 08 judges, whose experience as judges has been stipulated in over 02 years of exercise and that they work with accumulation of function of manager of the work unit. We observed that judges do indeed understand that management is also part of the daily work component and that this accumulation has generated tensions and repercussions on health. We noticed that the quantitative goals and processes for judgment have raised the workload, besides having a direct impact on health, generating psychic overload and decreasing social time. Finally, we have found that satisfaction for the resolution of conflicts and the sense of justice are factors that trigger pleasure in the work; the negative exposure of the image by the media, threats, the non-recognition of the effort at work and the lack of knowledge of the number of accumulated processes are factors of suffering.